Advances in Copper, Copper Alloys and Their Processing - Ulrich Prahl; Andreas Zilly; Julia Dölling (Metals)
Copper, renowned for its exceptional electrical and thermal conductivity, preferable technological properties, and recyclability, plays a pivotal role in various industries, from electronics and energy to transportation and construction [...]